Correction to: Kallistatin inhibits tumour progression and platinum resistance in high-grade serous ovarian cancer - Huan Wu; Rongrong Li; Zhiwei Zhang; Huiyang Jiang; Hanlin Ma; Cunzhong Yuan; Chenggong Sun; Yingwei Li; Beihua Kong (Journal of Ovarian Research, 2020)
The original article [1] contains errors in Fig. 3C, Results and Discussion.